Quantum Chemical Studies on the Corrosion Inhibition of Mild Steel by Piperidin-4-One Derivatives in 1 M H3PO4 - Kathirvel, Kalaiselvi; Thirumalairaj, Brindha; Jaganathan, Mallika (Scientific Research, 2014)
The corrosion inhibition properties of 2,6-diphenylpiperidin-4-one (DPP) (1A) and 2,6-diphenyldihydro-2H-thiopyran-4(3H)-one (DPDT) (1B) for mild steel in 1 M phosphoric acid were studied using weight loss, potentiodynamic polarization and electrochemical impedance spectroscopic techniques. The effect of temperature on the corrosion behavior of mild steel has been examined in the temperature range 303 - 328 K. The inhibition efficiency increases with increasing inhibitor concentration but decreases with increasing temperature. Potentiodynamic polarization studies indicated the mixed nature of inhibitors. The adsorption of the inhibitors on mild steel surface obeyed the Langmuir adsorption isotherms. The density functional theory (DFT) at the B3LYP/6- 31G (d) basis set level was performed on 1A and 1B to investigate the correlation between molecular structure and the corresponding inhibition efficiency (%). The quantum chemical parameters such as EHOMO, ELUMO, the energy gap (E), hardness (η), softness (S), dipole moment (µ), electron affinity (A), ionization potential (I), the absolute electronegativity (χ), the fraction of electron transferred (N), electrophilicity index (ω), the back-donation (EBack-donation) and Mulliken population analysis have been calculated.
Keywords: 2,6-Diphenylpiperdin-4-One Derivatives; Corrosion; Mild Steel; Phosphoric Acid; Density Functional Theory (DFT)